Effects of Perianeurysmal Environment during the Growth of Cerebral Aneurysms: A Case Study - Sforza, D.M.; Putman, C.M.; Tateshima, S.; Viñuela, F.; Cebral, J.R. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: The natural history of cerebral aneurysms is thought to be governed by multifactorial processes involving hemodynamics, biomechanics, mechanobiology, and perianeurysmal environment. The purpose of this study was to highlight the importance of considering the influence of contacts with perianeurysmal environment structures on the hemodynamics and geometric evolution of intracranial aneurysms. MATERIALS AND METHODS: A large aneurysm of the basilar artery in contact with bone and observed to grow during a 4-year follow-up period was selected for study. Anatomic models were constructed from longitudinal CTA images acquired at 1-year intervals during the observation period. Computational fluid dynamics simulations were carried out under pulsatile flow conditions to analyze the blood flow pattern and WSS distribution in the aneurysm during its evolution. RESULTS: The aneurysm was observed to grow against the bone, resulting in a geometric change of the proximal parent artery, which, in turn, induced substantial changes in the aneurysm hemodynamics. In particular, a region of elevated WSS created by the inflow streams was observed to shift locations around the place where the aneurysm enlarged in contact with the bone as the aneurysm progressed. In addition, a “notch” near the distal end of the aneurysm, away from the bone and subject to relatively high WSS, was observed to grow and, later, completely disappear. CONCLUSIONS: Contacts with perianeurysmal structures need to be considered and analyzed to assess whether they could exert a significant influence on the geometric evolution of each individual intracranial aneurysm and its hemodynamics. CFDcomputational fluid dynamicsWSSwall shear stress